Does the Digitalization of Public Services Influence Economic and Financial Crime? - Brici Iulia; Achim Monica Violeta (Studies in Business and Economics, 2023)
The aim of our research is to check if public services’ digitalization has an influence on economic and financial crime. We split economic and financial crime into its main forms and measured them using relevant indicators. For public services’ digitalization we consider indicators regarding online services’ quality, telecommunication infrastructure and e-government involvement. We also consider control variables that might affect the nexus between the main variables. Our sample comprise 185 countries, being split by developed and developing countries. Our processings are done in Eviews7, using Panel Least Squared Method. We test the relationship between public services’ digitalization and each component of economic and financial crime. The conclusions show a decrease of economic and financial crime with an increase of public services’ digitalization. In some particular cases, for developing countries we can observe a slight increase of the phenomenon. Our study completes the specialized literature because it includes a wider sample and a more complex set of indicators. It can also be very useful in developing national strategies and policies regarding the economic and financial crime issue. Digitalization is not a cause for concern when law is respected. If we have functional policies, technology will become citizen’s most accessible tool.